Czynniki wzrostu gospodarczego Polski w świetle neoklasycznego modelu wzrostu - Nazarczuk, Jarosław Michał; Marks-Bielska, Renata (Determinants of Economic Growth in Poland According to the Neoclassical Growth Model, 2009)
The aim of this paper is to identify main factors and tendencies of growth in the Polish economy as well as its potential directions of growth in the times of financial crisis. The analysis is based on one of neoclassical models of growth, mainly the Solow model with Cobb-Douglas production function and data published in Raport o stanie gospodarki. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 266-273